Simulation on spin wave transmission and domain wall dynamics in a permalloy nanostrip - Jain, Ravish K.; Tsai, Li-Zai; Huang, Bo-Chien; Chang, Liang-Juan; Liang, Jun-Zhi; Tang, Yu-Hui; Lee, Shang-Fan (Journal of magnetism and magnetic materials, 2022)
•Micromagnetic simulation study on permalloy nanostrip.•Transmission of spin waves through domain wall and spin wave induced domain wall motion.•The spatial oscillations of domain wall along the length of nanostrip are dependent upon the frequency and amplitude of the spin waves.•Correlation between the orientation of magnetization inside the domain wall, domain wall motion and spin wave transmission.•With increase in frequency of spin waves the spin wave transmission through domain wall tend to be isotropic and independent of orientation of magnetization inside the domain wall. Spin waves (SWs), the magnons, can potentially be used for fast and energy efficient information processing and the interaction of SWs with a magnetic domain wall (DW), which is quite complex, can play a key role in the development of magnonic devices. Manipulation of SW amplitude and phase is the key step in realization of spin wave devices. The SW transmission through DW is strongly dependent on the magnetization angle inside the DW and spatial movement of DW is coupled to this interaction. Magnonic spin transfer torque and linear momentum transfer of SW, collectively, control the motion of the DW and the rotation of magnetization inside the DW. In the present work, micromagnetic simulations were performed considering a ferromagnetic permalloy nanostrip with perpendicular magnetic anisotropy (PMA) using mumax3 platform to study SW transmission through DW. The correlation between rotation in magnetization tilt angle (δϕ) inside an initially Néel-type DW and SW-transmission ratio (TD) was investigated at different SW-frequencies ranging from 18 GHz to 28 GHz. Applied SW amplitude at each frequency was sufficiently large for transverse DW to show oscillatory motion along the length of the strip. The results showed that the dependence of TD on rotation in magnetization angle (δϕ) decreases as the frequency of SW is increased and it approaches a nearly isotropic behavior at higher frequencies.